Protamine nanocapsules as gene delivery carriers for the treatment of intraocular tumors - Sheila Barrios-Esteban; Ignacio Alcalde; Manuel Chacón; Jesús Merayo-Lloves; María de la Fuente; Noemi Csaba (Drug Delivery and Translational Research, 2026)
Uveal melanoma is the most common primary intraocular tumor in adults that appears mainly in the choroid, ciliary body, or iris. Standard non-surgical treatment consists of radiotherapy and chemotherapy by intravitreal injection of drugs, which is hampered by unpleasant side effects and high recurrence rate. As an alternative strategy, gene therapy has the capacity of targeting specific pathways in cancer cells by introducing tumor suppressor sequences that are rendered therapeutically effective by the use of suitable delivery vectors. In this paper, we describe the development of protamine nanocapsules as potential gene delivery carriers to the eye by its topical administration. These nanocapsules, composed of spherical oily nano-droplets surrounded by a protamine shell with small particle size (≤ 250 nm) and positive surface charge (+ 33 mV), can efficiently associate different nucleic acids such as pDNA and miRNA, and release them in biorelevant media. In vitro studies evidenced their low cytotoxicity and efficient internalization with 36% of TAMRA-positive cells, and transfection capacity from doses of 0.5 µg of pDNA in uveal melanoma cells. Finally, the results also confirmed their efficient interaction and permeation in primary patient-derived 3D corneal models with a reduction of up to 60% in TEER values, without altering the structure of this ocular barrier. Graphical abstract

Changes in solution turbidity and color during paracetamol removal in laboratory and pilot-scale semicontinuous ozonation reactors - Natalia Villota; Alberto Cruz-Alcalde; Cristian Ferreiro; José Ignacio Lombraña; Santiago Esplugas (Science of The Total Environment, 2023)

Polymeric nanocapsules: a potential new therapy for corneal wound healing - Sonia Reimondez-Troitiño; Ignacio Alcalde; Noemi Csaba; Almudena Íñigo-Portugués; María de la Fuente; Federico Bech; Ana C. Riestra; Jesús Merayo-Lloves; María J. Alonso (Drug Delivery and Translational Research, 2016)